Inducing transient enantiomeric excess in a molecular quantum racemic mixture with microwave fields - Sun, Wenhao; Tikhonov, Denis S.; Singh, Himanshi; Steber, Amanda L.; Pérez, Cristóbal; Schnell, Melanie (Nature communications, 2023)
Chiral molecules with low enantiomer interconversion barriers racemize even at cryogenic temperatures due to quantum tunneling, forming a racemic mixture that is impossible to separate using conventional chemical methods. Here we both experimentally and theoretically demonstrate a method to create and probe a state-specific enantiomeric enrichment for such molecular systems. The coherent, non-linear, and resonant approach is based on a microwave six-wave mixing scheme and consists of five phase-controlled microwave pulses. The first three pulses induce a chiral wavepacket in a chosen rotational state, while the consecutive two pulses induce a polarization for a particular rotational transition (listen transition) with a magnitude proportional to the enantiomeric excess created. The experiments are performed with the transiently chiral molecule benzyl alcohol, where a chiral molecular response was successfully obtained. This signal demonstrates that enantiomeric excess can be induced in a quantum racemic mixture of a transiently chiral molecule using the developed microwave six-wave mixing scheme, which is an important step towards controlling non-rigid chiral molecular systems. There is growing interest in controlling and manipulating molecules using external field. Here the authors demonstrate microwave induced transient enantiomeric excess in a state-selective benzyl alcohol using microwave six-wave mixing.